2017
DOI: 10.21834/e-bpj.v2i5.619
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to the Automation of Building Performance Simulation: Adaptive Building Integrated Photovoltaic (BIPV) design

Abstract: Building Integrated Photovoltaic (BIPV) is one of the most promising renewable energy technologies. A BIPV system as a second layer of building envelopes is useful not only for the electric power generation but also for blocking solar radiation to reduce cooling load. This study aimed to explore the limitations of the automated BPS of an adaptive BIPV case study that its development conducted through a collaboration of a BIM software, a BIM-integrated visual programming environment, and a cloud-based energy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Published research has shown the outstanding possibilities of BEM for the energetic simulation of infrastructure [34,35]. Those BEM techniques permit connecting BIM models with external databases which collect the main material properties, allowing a detailed energetic analysis [34].…”
Section: Bim and Energy Managementmentioning
confidence: 99%
“…Published research has shown the outstanding possibilities of BEM for the energetic simulation of infrastructure [34,35]. Those BEM techniques permit connecting BIM models with external databases which collect the main material properties, allowing a detailed energetic analysis [34].…”
Section: Bim and Energy Managementmentioning
confidence: 99%
“…An interoperable, intelligent and object-oriented simulation model would enable bi-directional data exchange with a Building Information Modelling (BIM) authoring applications, reusing of geometric and other data from different models significantly reduces the overhead associated with the definition of input data and has the potential to eliminate error-prone manual processes (O'Donnell, et al, 2011;Ning, et al, 2017). Nowadays, it is generally accepted by the Architecture, Engineering, Construction, and Operations (AECO) industries that Building Information Modeling (BIM) is the most promising technology for enhancing the performance and quality of construction (Kuo, Hsieh, Guo, & Chan, 2016;Somboonwit, Boontore, & Rugwongwan, 2017). A BIM is a tool / methodology / paradigm / process of virtual design and construction involving the generation and management of digital representations of physical and functional characteristics of a facility which creates and uses the coordinated, consistent, computable information of the 3D models of the project components interconnect with the holistic information that conceived as a source of shared knowledge to support decision-making, through the life cycle of the building.…”
Section: Automated Bps and Building Information Modeling (Bim)mentioning
confidence: 99%
“…13, No. 12 2017 to support the construction, fabrication, and procurement activities through which the building is realized (Krygiel & Nies, 2008;Kymmell, 2008;Eastman, Teicholz, Sacks, & Liston, 2011;Matthew, Jason, Melissa, Seokho, & Fiona, 2013;Ladenhauf, et al, 2015;Agugiaro, 2016;Kuo, Hsieh, Guo, & Chan, 2016;Somboonwit, Boontore, & Rugwongwan, 2017). There is a very useful feature of BIM is that building geometry can be extracted from a BIM model to support the assessment of alternative sustainable design principles.…”
Section: Automated Bps and Building Information Modeling (Bim)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the negative impact of buildings on the environment, which is the responsibility of the construction industry, the demand for sustainable buildings is increasing (Jose et al, 2019;Jensen et al, 2018, Chalal et al, 2020. Policymakers make the majority of critical decisions related to energy even before the design process starts (Chong et al, 2017;Kreider et al, 2010;Pinheiro et al, 2018;Somboonwit et al, 2017).…”
Section: Introductionmentioning
confidence: 99%